Technique for Order Preference by Similarity to Ideal Solution as Decision Support Method for Determining Employee Performance of Sales Section - N S Lestari, V; Djanggih, Hardianto; Aswari, Aan; Hipan, Nasrun; P U Siahaan, A (International Journal of Engineering and Technology, 2018)
Employees are the backbone of corporate activities and the giving of bonuses, job titles and allowances to employees to motivate the work of employees is very necessary, salesman on the company very much and to find the best salesman cannot be done manually and for that required the implementation of a system in this decision support system by applying the TOPSIS method, it is expected with the implementation of TOPSIS method the expected results of top management can be fulfilled.Â